2012
DOI: 10.1016/j.meegid.2012.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of full-length HIV-1 CRF17_BF genomes and comparison to the prototype CRF12_BF strains

Abstract: The aim of this work is to characterize the full-length intersubtype recombinant structure of the HIV-1 Circulating Recombinant Form CRF17_BF. A single genome of CRF17_BF was originally described in 2001 as being largely similar to CRF12_BF. Since then, more genomes of CRF17_BF have been sequenced but not adequately described in publications. Here we describe CRF17_BF as a genuine CRF, and analyze its recombination pattern based on bootscan analyses, subtype signature patterns, and phylogenetic reconstruction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Other CRF_BF have also been described in South America: CRF28_BF and CRF29_BF in Sao Paulo (Brazil) [ 10 ]; CRF39_BF and CRF40_BF in Rio de Janeiro (Brazil) [ 11 ]; CRF38_BF in Uruguay [ 12 ]; and CRF44_BF in Chile [ 13 ]. In Argentina after the identification of the CRF12_BF and CRF17_BF in 2001 [ 14 , 15 ], several studies showed that most BF recombinants circulating locally were closely associated with CRF12_BF or diverse BF recombinants related to it [ 1 , 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other CRF_BF have also been described in South America: CRF28_BF and CRF29_BF in Sao Paulo (Brazil) [ 10 ]; CRF39_BF and CRF40_BF in Rio de Janeiro (Brazil) [ 11 ]; CRF38_BF in Uruguay [ 12 ]; and CRF44_BF in Chile [ 13 ]. In Argentina after the identification of the CRF12_BF and CRF17_BF in 2001 [ 14 , 15 ], several studies showed that most BF recombinants circulating locally were closely associated with CRF12_BF or diverse BF recombinants related to it [ 1 , 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The designation of additional SIVs: mnd = Mandril ( Mandrillus sphinx ); drl = Drill ( Mandrillus leucophaeus ), col = colobus monkeys (Mantled guereza, Colobus guereza ), gsn = greater spot nosed monkey ( Cercopithecus nictitans ), mon = Mona monkey ( Cercopithecus mona ); mus = Moustached gueneon ( Cercopithecus cephus ); deb = De Brazza's monkey ( Cercopithecus neglectus ); lho = group of L'hoesti monkeys ( Cercopithecus l'hoest i); sun = sun tailed monkey ( Cercopithecus solatus ); syk = Sykes monkeys ( Cercopithecus albogularis ); tal = Gabon (Northern) talapoin ( Miopithecus oguensis ); wrc = western red colobus ( Procolobus badius ); agm = African green monkey ( Chlorocebus tantalus, C aethiops, C vervet ). The schema of the phylogenetic tree of primate Lentiviruses (SIV, HIV) was developed according to publications by Sharp and Hahn, 2011 [3]; Santiago et al, 2005 [32]; Aulicino et al, 2012 [110]; Aghokeng et al, 2010 [218] and Holmes et al, 1995 [219]. …”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%
“…Further recombinants are found in Brazil and in neighbouring countries [16]. Two other recombinant strains of the subtypes B and F (CRF12_BF and CRF17_BF) are circulating in Argentina [110]. …”
Section: Current Knowledge About the Pathogenmentioning
confidence: 99%
“…The full-length sequencing allowed the characterization of the recombinant CRF12_B/F1 together with other diverse URF_B/F1 7,8 , showing that almost all F1 strains, according to the env gene, were in fact recombinant forms with breaking points with subtype B in the pol gene. Other studies using only strains from Buenos Aires detected recombinants URF_B/F1, CRF16_A2D, B/D, B/C, B/K, B/A, CRF06_cpx, and a triple recombinant B/C/F 9,10,11,12,13 . The epidemic in Buenos Aires has been exhaustively studied, but little is known about the HIV-1 epidemic in the rest of Argentina.…”
Section: Introductionmentioning
confidence: 95%